Propagation of optical vortices in an add-drop resonator based on a vertical array of ring resonators - B.P. Lapin; E.V. Barshak; M.A. Yavorsky; C.N. Alexeyev (Компьютерная оптика)
In this paper we study the transmission of higher-order modes, including optical vortices (OVs), through a bus fiber evanescently coupled with a vertical array of ring resonators (VAR), which form a vertically stacked multi-ring resonator. It is shown that the OV transmission curves have a characteristic structure that we explain by the manifestation of the band structure of an infinite stack of coupled ring resonators. We demonstrate a fundamental possibility of using VARs as elements of delay lines for fiber-optic communications using orbital angular momentum. It is shown that the VAR is capable of serving as a delay line element for even and odd Laguerre–Gauss modes.